How to do better creative work - Harrison, Steve (Pearson, 2021)
Effective creative work is not a nice-to-have, it's a necessity - it's the only way you'll stand out in a fiercely competitive marketplace. Whether you're in digital, direct or advertising, the CEO of an agency or just starting out, How to do better creative work has been written for you.
Includes index
Keywords: Creative ability in business; Creative ability; Créativité dans les affaires; Créativité; creativity